Shaping the Change: the Evolution of Landscape Representation and the Relationship between Man and Nature (diségno, 2024)
The representation of landscape has evolved in parallel with the relationship between humans and nature. Initially, nature was seen as a static material world. This romantic and picturesque vision changed with Darwin’s Theory of Natural Selection, which integrated humans into the ecosystem. The introduction of the term ‘ecology’ by Haeckel in 1866 further emphasized the bond between humans and nature, highlighting species interdependence and ecological balance.This conceptual evolution was reflected in landscape architecture, moving from aesthetic drawings to complex diagrams that depict the dynamics of natural systems. Contemporary designers use everything from quick sketches to detailed diagrams that illustrate natural processes and their interactions with the built environment.Over time, landscape drawings have transfigured landscape architecture, blending technical information with profound artistic and historical sensitivity. Architects and artists like Ian McHarg, Lawrence Halprin, Christo and Jeanne-Claude, Diana Balmori, Robert Smithson, Bernard Lassus, James Corner, and Kongjian Yu have used drawing to explore and communicate new ideas about nature and landscapes. The proposed text will analyze this evolution and how contemporary drawings reflect an integration of scientific, aesthetic, and cultural approaches in landscape representation.
Keywords: evolution of landscape design; landscape drawing; contemporary landscape architecture; ecology